Can the utility value of educational sciences be induced based on a reflection example or empirical findings—Or just somehow? - Rochnia, Michael; Gräsel, Cornelia (Frontiers in Education, 2022)
Educational sciences are a central content of German teacher education. But student teachers often do not consider educational sciences in university courses (a profession-specific combination of educational psychology, pedagogy and sociology) as helpful for the practice of teaching. In order to prepare future teachers for evidence-based practice, this is an unfavorable motivational starting point, because educational sciences offer a large amount of current and relevant findings that can have positive impact on educational practice. Thus, it would be beneficial if student teachers could see the utility value of educational sciences. The present study attempts to encourage student teachers to perceive the utility value of educational sciences with a utility value short intervention. Utility value interventions contribute to connecting the learning content with one's own life in order to foster motivation to use scientific knowledge. A 2 × 2 quasi-experiment was conducted. Two of the four groups received a utility value short intervention about educational sciences (Factor 1). In addition, a second factor was analyzed that takes up two important patterns of educational reasoning in teacher education (Factor 2): Reasoning was either exemplified with an instruction to reflect on the usefulness of educational sciences (like in reflection-oriented educational reasoning) or with exemplary empirical findings from educational sciences (like in evidence-based educational reasoning). These two kinds of reasoning are aims of teacher education and therefore could influence the effect of a utility value short intervention. Since epistemic goals influence the engagement with educational science, these are also taken into account. The results showed that all four variants of the treatment increased the students’ assessment of the utility value of educational sciences; the utility value intervention had no additional effect. This is discussed with recourse of motivational theories and concepts of teacher education.